HISTORY OF EMERGENCY MEDICAL SERVICES IN UZBEKISTAN FROM 1925 TO 1991 YY - Ergasheva Mukhliса Soatullaevna (Bright Mind Publishing, 2025)
This article analyzes the formation, development, and functioning of emergency medical services (EMS) in Uzbekistan from 1925 to 1991 based on historical sources and scientific literature. It provides a detailed examination of issues related to staffing, the activities and specialization of ambulance stations, training programs, and improvements in service quality. Additionally, the impact of the country’s socio-political and economic conditions on the emergency medical services sector is also highlighted.
Keywords: Emergency medical services, ambulance station, doctor, paramedic, training, specialization.